The Psycho-Social Impact on Hearing Children of Deafness in Their Primary Caregiver - Ward, Anna (Auckland University of Technology, 2009)
This study examines whether deafness in the caregiver impacts on the development and socialisation of their hearing child. Therefore this dissertation is guided by the question: “Can deafness in the primary caregiver be linked to a characteristic psychological profile in the hearing child and if so what are the characteristics of this profile?” When thinking about the hearing child/deaf caregiver dyad many questions arise surrounding the possible impact of the deaf/hearing relationship on the child’s development: How does the deaf caregiver respond to the infant when the caregiver can not hear the child? How do they communicate with each other? How does the child adapt to a bilingual role? Does the child become an intermediary between the deaf and hearing worlds and can this lead to undesirable complications to their development? This study sets out to examine these questions and to provide a profile for psychotherapists who work with this unique population. Ideas and solutions for deaf caregivers of hearing children who have asked these questions are also addressed in this study.
Keywords: Deaf caregiver; Psychotherapy; Hearing children